2020
DOI: 10.1177/0954406220910445
|View full text |Cite
|
Sign up to set email alerts
|

An experimental investigation of the fabrication of biodegradable zinc–hydroxyapatite composite material using microwave sintering

Abstract: The present work focuses on the fabrication of zinc–hydroxyapatite biodegradable composite with the use of pressureless microwave sintering for the orthopedic load-bearing application. The samples were prepared using the powder metallurgy process. The powders of both materials were homogeneously mixed in the quantified proportions to form the uniform mixture. For the fabrication of samples, the planning of experiments was done with the central composite design. The effect of process factors such as th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
18
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 22 publications
(18 citation statements)
references
References 41 publications
(61 reference statements)
0
18
0
Order By: Relevance
“… Composition &Fabrication Corrosion medium Immersion time (day) Corrosion properties Ref. Icorr (μA/cm 2 ) Ecorr (V) C.R (elec) (mm/y) C.R (imm) (mm/y) Zn SPS HBSS 50 4.900 ± 2.810 −0.942 ± 0.075 0.073 ± 0.042 0.0048 [ 91 ] Zn-1HA SPS 50 21.076 ± 3.251 −1.281 ± 0.037 0.327 ± 0.050 0.0026 Zn-5HA SPS 50 39.127 ± 0.661 −1.274 ± 0.005 0.630 ± 0.011 0.0101 Zn-10HA SPS 50 51.044 ± 1.803 −1.290 ± 0.010 0.856 ± 0.031 0.0250 Zn HE SBF 14 0.15 [ 305 ] Zn-8HA HE 14 0.40 Zn-3HA PM 5.164 −1.070 0.084 ± 0.012 [ 310 ] ...…”
Section: Zn-based Compositesmentioning
confidence: 99%
“… Composition &Fabrication Corrosion medium Immersion time (day) Corrosion properties Ref. Icorr (μA/cm 2 ) Ecorr (V) C.R (elec) (mm/y) C.R (imm) (mm/y) Zn SPS HBSS 50 4.900 ± 2.810 −0.942 ± 0.075 0.073 ± 0.042 0.0048 [ 91 ] Zn-1HA SPS 50 21.076 ± 3.251 −1.281 ± 0.037 0.327 ± 0.050 0.0026 Zn-5HA SPS 50 39.127 ± 0.661 −1.274 ± 0.005 0.630 ± 0.011 0.0101 Zn-10HA SPS 50 51.044 ± 1.803 −1.290 ± 0.010 0.856 ± 0.031 0.0250 Zn HE SBF 14 0.15 [ 305 ] Zn-8HA HE 14 0.40 Zn-3HA PM 5.164 −1.070 0.084 ± 0.012 [ 310 ] ...…”
Section: Zn-based Compositesmentioning
confidence: 99%
“…Second, it resulted in the increased random microvoids with the higher weight percentage of HA in Zn matrix due to lower sintering temperature and lack in the interfacial reaction between Zn and HA. [32,33,52] These microvoids significantly activated the penetration of the corrosive fluid in the composite samples, thereby increasing the corrosion rate of the composite samples with a high wt% of HA in the Zn matrix. Furthermore, the incorporation of Fe in the Zn-HA matrix led to produce micro galvanic effects to prompt the degradation more.…”
Section: Discussionmentioning
confidence: 99%
“…In the present work, pure Zn, Zn‐3HA, Zn‐3HA‐2Fe, and Zn‐5HA‐2Fe samples were prepared with the aforesaid mentioned methodology. The weight percentage ( wt %) of HA was decided based on the authors' previous work, [ 33 ] which demonstrated the compressive yield strength (CYS) of the Zn‐HA composites decreased beyond 6 wt % of HA. In order to confirm the wt % of Fe in Zn‐HA matrix, pilot experiments were carried out with the optimized process factors mentioned above.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations